DEVELOPING THEMATIC LEARNING MODULE TO IMPROVE CRITICAL THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Awalina Barokah; Titin Sunaryati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to produce a thematic learning module to improve students’ critical thinking skills. This research was research and development. The development procedures were adapted from Borg & Gall model. The data were collected through interviews (need analysis), test, observation, and questionnaire. The product was validated by media experts, material experts, linguistics experts. Data were analyzed by using MANOVA test with significance level of 5%. The result showed that based on media experts, material experts, and linguistics experts, the thematic learning module was feasible to be used with “very good” category and the thematic learning module was effective to improve students’ critical thinking skill with “good” category.